Hepatoprotective activity of methanol extract of Asteracantha longifolia in rats (Journal of Laboratory Animal Science, 2019)
The study was conducted to assess the hepatoprotective activity of Asteracantha longifolia in carbon tetra chloride (CCl4) induced hepatotoxicity in rats. The hepatoprotective effect of methanolic extract of whole  plant of Asteracantha longifolia was studied by monitoring serum aspartate amino transferase (AST), serum  alanine amino transferase (ALT) and histopathological alterations. Pre-treatment with methanol extract of  Asteracantha longifolia in rats treated with CCl4 showed a significant inhibition (P
Keywords: Asteracantha longifolia; methanol; hepatoprotective; carbontetrachloride; silymarin